2023
DOI: 10.1038/s41598-023-32330-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for ZnO@NiO core–shell nanoparticle synthesis using pulse laser ablation in liquid and plasma jet techniques

Abstract: Given their versatile nature and wide range of possible applications, core–shell nanoparticles (NPs) have received considerable attention. This paper proposes a novel method for synthesizing ZnO@NiO core–shell nanoparticles using a hybrid technique. The characterization demonstrates the successful formation of ZnO@NiO core–shell nanoparticles, which have an average crystal size of 13.059 nm. The results indicate that the prepared NPs have excellent antibacterial activity against both Gram-negative and Gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…From Fig. 2 (b), E g values are 3.16, and 3.07 eV for Green-ZnO, and ZnO-Chem respectively 47 49 . It denotes a widening of the optical BG for the Green-ZnO compared to Chem-ZnO.…”
Section: Resultsmentioning
confidence: 92%
“…From Fig. 2 (b), E g values are 3.16, and 3.07 eV for Green-ZnO, and ZnO-Chem respectively 47 49 . It denotes a widening of the optical BG for the Green-ZnO compared to Chem-ZnO.…”
Section: Resultsmentioning
confidence: 92%
“…In recent years, a new class of hybrid NPs has been developed, namely, core-shell NPs, which comprise two or more single nanomaterial types [12,13]. Researchers have found that the majority of NPs' physical characteristics are dependent on their nanostructured surface due to the characteristics of NPs that assist in enhancing the number of dangling bonds, which influences their physicochemical qualities [14]. These features could be improved even further by using a coating material to build the outer shell of this nanostructured form.…”
Section: Introductionmentioning
confidence: 99%
“…6 For many of these applications, NiO must be deposited as a thin film with a well-regulated microstructure. There are several physical and chemical approaches including sputtering, 7 pulsed laser deposition, 8 electron-beam evaporation 9 and sol-gel, 10 spray pyrolysis 11 and anodic deposition 12 that have been used to synthesize NiO films, respectively. In comparison to other synthesis approaches, the sol-gel method has several advantages, including cost effectiveness, straightforward implementation, high quality thin films, and the synthesis of films with significant surface areas.…”
mentioning
confidence: 99%